(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The main objectiveof research work is to study, Vocational Interest as determined by creativitycomponents, scholastic Achievement and sex of 160 students of inter classes ofboth the sexes. In conclusion, (i) Artistic Interest is more dominant infemale which have low on flexibility and high on scholastic Achievement. (ii) When flexibility scholastic Achievementsex all three taken separately, flexibility when taken with scholasticAchievement and flexibility, scholastic Achievement, sex all the three whentaken together do not affect Artistic Interest.